MR-safety in clinical practice at 7T: Evaluation of a multistep screening process in 1819 subjects. Issue 2 (May 2022) - Hansson, B.; Simic, M.; Olsrud, J.; Markenroth Bloch, K.; Owman, T.; Sundgren, P.C.; Björkman-Burtscher, I.M.
Abstract: Introduction: MR facilities must implement and maintain adequate screening and safety procedures to ensure safety during MR examinations. The aim of this study was to evaluate a multi-step MR safety screening process used at a 7T facility regarding incidence of different types of safety risks detected during the safety procedure. Methods: Subjects scheduled for an MR examination and having entered the 7T facility during 2016–2019 underwent a pre-defined multi-step MR safety screening process. Screening documentation of 1819 included subjects was reviewed, and risks identified during the different screening steps were compiled. These data were also related to documented decisions made by a 7T MR safety committee and reported MR safety incidents. Results: Passive or active implants (n = 315) were identified in a screening form and/or an additional documented interview in 305 subjects. Additional information not previously self-reported by the subject, regarding implants necessitating safety decisions performed by the staff was revealed in the documented interview in 102 subjects (106 items). In total, the 7T MR safety committee documented a decision in 36 (2%) of the included subjects. All of these subjects were finally cleared for scanning. Conclusion: A multi-step screening process allows a thorough MR screening of subjects, avoiding safety incidents. Different steps in the process allow awareness to rise and items to be detected that were missed in earlier steps. Implications for practice: Safety questions posed at a single timepoint during an MR screening process might not reveal all safety risks. Repetition and rephrasing of screening questions leads to increased detection of safety risks. This could be effectively mitigated by a multi-step screening process. A multi-disciplinary safety committee is efficient at short notice responding to unexpected safety issues.